Can the 2011 East African drought be attributed to human‐induced climate change?. Issue 6 (27th March 2013) - Lott, Fraser C.; Christidis, Nikolaos; Stott, Peter A.
Abstract: [1] This study applies the technique of event attribution to the East African rainy seasons preceding the drought of 2011. Using observed sea surface temperatures (SSTs), and sea ice conditions with a state‐of‐the‐art atmosphere model, the precipitation totals during late 2010 (the "short rains") and early 2011 (the "long rains") were simulated hundreds of times to produce possible distributions of precipitation. Alternative distributions of precipitation were produced, consistent with a world with neither anthropogenic forcings nor human influence on SSTs and sea ice. Comparing these modeled distributions to the observed rainfall, no evidence was found for human influence on the 2010 short rains, with their failure being affected by La Niña. However, human influence was found to increase the probability of long rains as dry as, or drier than, 2011. The magnitude of increase in probability depends on the estimated pattern by which human influence changed observed SSTs. Key Points: Changes in the probability of failure of East African rainy seasons are examined 2010 short rains failure shows strong influence from La Niña 2011 long rains failure was made more probable due to human influence